Outcome evaluation of climate-smart research on solar-powered irrigation in India - Douthwaite, Boru; Shepherd, Keith D. (CGIAR Research Program on Water, Land and Ecosystems, 2020)
This summary extracts the conclusions and recommendations from an evaluation of the outcomes from the work of the CGIAR Research Programs (CRP) on Water, Land and Ecosystems (WLE) and Climate Change, Agriculture and Food Security (CCAFS). It is intended to serve as a stand-alone summary, as well as to direct readers to a more detailed description of the methodology, evidence and findings in the main report.